Pigment dispersion composition for black matrix, resist composition for black matrix, and black matrix
Patent Information
- Application Number
- JP2024216482
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2040-11-25
AI Technical Summary
【0014】 本発明によれば、高温かつ長時間のポストベークをしたとしても表面抵抗値が低下しないブラックマトリックスを形成することができ、かつ、保存時間によってブレークポイントが変化しないブラックマトリックス用レジスト組成物を得ることができるブラックマトリックス用顔料分散組成物を提供することができる。
Smart Images

Figure 2025028138000001 
Figure 2025028138000002 
Figure 2025028138000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pigment dispersion composition for a black matrix, a resist composition for a black matrix, and a black matrix. [Background technology]
[0002] In image display devices using liquid crystal or plasma, etc., a light-shielding film (black matrix) is provided in the gaps between colored patterns within the display area of the screen, around the edges of the display area, and in liquid crystal displays using TFTs, on the external light side of the TFT. In LCD displays, it mainly prevents light leakage from the backlight from appearing on the screen, and in plasma displays, it mainly prevents blurring caused by the mixing of various colored lights from appearing on the screen, thereby improving display characteristics (contrast and color purity).
[0003] For example, color filters used to convert the white light of a backlight in a liquid crystal display device into colored light are usually manufactured by forming pixels of different hues, red, green and blue, in sequence in a striped or mosaic pattern on the surface of a transparent substrate, such as glass or a plastic sheet, on which a black matrix has been formed.
[0004] Similarly, in touch panels that combine image display devices and position input devices, color filters with black matrices formed as light-shielding films are also used, and up until now, they have generally been formed on the opposite side of the cover glass to the sensor substrate. However, as the demand for lighter touch panels increases, progress is being made in the development of technology to simultaneously form the light-shielding film and touch sensor on the same side of the cover glass in order to achieve even lighter weight.
[0005] As a method for forming such a black matrix, for example, a photolithography method using a pigment (pigment method) is used. In such a pigment method, a sulfonic acid derivative of copper phthalocyanine is sometimes used to improve the dispersibility of the pigment.
[0006] For example, Patent Document 1 discloses a pigment dispersion composition for black matrices, which is characterized in that carbon black having an oil absorption in the range of 10 to 150 ml / 100 g and a pH of more than 9, a basic group-containing urethane-based polymer pigment dispersant having a polyester chain, and a phthalocyanine derivative having a sulfonic acid group as an acid group-containing pigment derivative are dispersed in a solvent.
[0007] In recent years, image display devices have come to be used in a variety of situations, including for mobile purposes. As the uses of such image display devices expand, a stronger black matrix is required.
[0008] As a method for making the black matrix stronger, a method of post-baking at a high temperature for a long period of time is sometimes used. However, in Patent Document 1, the decrease in surface resistance caused by performing post-baking at high temperature for a long period of time is not fully considered, and there is room for further improvement.
[0009] On the other hand, a pigment dispersion resist composition for a black matrix is required to have a performance that does not change the breakpoint (the time at which the unexposed portion dissolves and peels off in the development process and the developed pattern begins to appear) depending on storage time. Therefore, there is a demand for a pigment dispersion composition for black matrix that can obtain such a pigment dispersion resist composition for black matrix. However, Patent Document 1 does not fully consider the matter, and there is room for further improvement. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] International Publication No. 2008 / 066100 Summary of the Invention [Problem to be solved by the invention]
[0011] Therefore, an object of the present invention is to provide a pigment dispersion composition for a black matrix which can form a black matrix whose surface resistance value does not decrease even when post-baked at high temperature for a long period of time, and which can obtain a resist composition for a black matrix whose break point does not change depending on storage time. [Means for solving the problem]
[0012] The present inventors have found that a pigment dispersion composition for a black matrix, which contains a black colorant, a sulfonated copper phthalocyanine, and an epoxy compound, can form a black matrix whose surface resistance value does not decrease even when post-baked at high temperature for a long period of time, and can also obtain a resist composition for a black matrix whose break point does not change depending on the storage time, and have completed the present invention.
[0013] That is, the present invention is a pigment dispersion composition for a black matrix, which contains a black colorant, a sulfonated copper phthalocyanine, and an epoxy compound. The epoxy compound preferably has a bisphenol skeleton. Moreover, it is preferable that the pigment dispersion composition for black matrix of the present invention further contains an amine compound having a molecular weight of 300 or less, and that the amine compound having a molecular weight of 300 or less is an amine compound having a secondary or higher carbon atom within 3 atoms from the nitrogen atom of the amino group and / or an amine compound in which the amino group is connected to one or more aromatic rings via a hydrocarbon group having 3 or less carbon atoms. The amine compound having a molecular weight of 300 or less is preferably at least one selected from 3-phenylpropylamine, 1,1,3,3-tetramethylbutylamine, and triisobutylamine. The sulfonated copper phthalocyanine preferably has 0.5 to 3 sulfonic acid groups in the molecule, and more preferably has 0.5 to 1.5 sulfonic acid groups. The black colorant preferably contains carbon black. The carbon black is preferably acidic carbon black. The present invention also relates to a resist composition for a black matrix obtained from the above-mentioned pigment dispersion composition for a black matrix. The present invention also relates to a black matrix formed from the above-mentioned black matrix resist composition. Effect of the Invention
[0014] According to the present invention, it is possible to provide a pigment dispersion composition for a black matrix which can form a black matrix whose surface resistance value does not decrease even when post-baked at high temperature for a long period of time, and which can obtain a resist composition for a black matrix whose break point does not change depending on storage time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] <Pigment dispersion composition for black matrix> The pigment dispersion composition for black matrix of the present invention contains a black colorant, a sulfonated copper phthalocyanine, and an epoxy compound, and satisfies the following condition (A) or (B). (A) Contains no amine compounds with a molecular weight of 300 or less. (B) Further containing an amine compound having a molecular weight of 300 or less, the amine compound having a molecular weight of 300 or less is an amine compound having a secondary or higher carbon atom within 3 atoms from the nitrogen atom of the amino group and / or an amine compound in which the amino group is connected to one or more aromatic rings via a hydrocarbon group having 3 or less carbon atoms. Each component will be described below.
[0016] (Black colorant) The pigment dispersion composition for a black matrix of the present invention contains a black colorant. The black colorant preferably contains carbon black, and the carbon black is more preferably acidic carbon black. The carbon black preferably has an average primary particle diameter of 20 to 60 nm, and more preferably is neutral carbon black with an average primary particle diameter of 20 to 60 nm and / or acidic carbon black with an average primary particle diameter of 20 to 60 nm. When the primary particle size of the black colorant is smaller than 20 nm or larger than 60 nm, the light-shielding property may be insufficient and the storage stability may be poor. The above average primary particle size is an arithmetic mean diameter value determined by observation with an electron microscope.
[0017] From the viewpoint of imparting a suitable surface resistivity, the black colorant preferably contains only acidic carbon black. On the other hand, when the neutral carbon black and the acidic carbon black are used in combination, the neutral carbon black preferably accounts for 85 mass% or less, and more preferably 75 mass% or less, of the total mass of the neutral carbon black and the acidic carbon black. If the neutral carbon black content in the carbon black is more than 85% by mass, the seal strength may decrease.
[0018] The above-mentioned acidic carbon black and neutral carbon black will now be described. Carbon black can be broadly classified into acidic carbon black and neutral carbon black based on the surface structure. Acidic carbon black is a carbonaceous material that is naturally or artificially oxidized and exhibits acidity when mixed and boiled with distilled water. On the other hand, neutral carbon black is known to exhibit a neutral or higher pH when mixed and boiled with distilled water.
[0019] The neutral carbon black preferably has a pH in the range of 8.0 to 10.0. Specific examples include Printex 25 (average primary particle diameter 56 nm, pH 9.5), Printex 35 (average primary particle diameter 31 nm, pH 9.5), Printex 65 (average primary particle diameter 21 nm, pH 9.5), manufactured by Orion Engineered Carbons, and MA#20 (average primary particle diameter 40 nm, pH 8.0), MA#40 (average primary particle diameter 40 nm, pH 8.0), MA#30 (average primary particle diameter 30 nm, pH 8.0), manufactured by Mitsubishi Chemical Corporation.
[0020] The acidic carbon black preferably has a pH in the range of 2.0 to 4.0. Specific examples of the acidic carbon black include Raven 1080 (average primary particle size 28 nm, pH 2.4) and Raven 1100 (average primary particle size 32 nm, pH 2.9) manufactured by Columbia Chemicals, MA-8 (average primary particle size 24 nm, pH 3.0) and MA-100 (average primary particle size 22 nm, pH 3.5) manufactured by Mitsubishi Chemical, Special Black 250 (average primary particle size 56 nm, pH 3.0), Special Black 350 (average primary particle size 31 nm, pH 3.0), Special Black 550 (average primary particle size 25 nm, pH 4.0), and NEROX 305 (average primary particle size about 28 nm, pH about 2.8) manufactured by Orion Engineered Carbons, and the like.
[0021] As the black colorant, from the viewpoint of providing favorable pigment dispersibility and surface resistance value, Special Black 250 or NEROX305 is preferable.
[0022] The pH can be measured by adding 1 g of carbon black to 20 ml of decarbonated distilled water (pH 7.0) and mixing with a magnetic stirrer to prepare an aqueous suspension, and using a glass electrode at 25°C (German Industrial Standard DIN ISO 787 / 9).
[0023] The content of the black colorant is preferably from 3 to 70% by mass, and more preferably from 10 to 50% by mass, as a mass fraction relative to the total solid content of the pigment dispersion composition for black matrix of the present invention. If the content of the black colorant is less than 3% by mass, the light blocking properties may be reduced when a black matrix is formed, whereas if it exceeds 70% by mass, it may become difficult to disperse the pigment.
[0024] (Sulfonated copper phthalocyanine) The pigment dispersion composition for black matrix of the present invention contains a sulfonated copper phthalocyanine. In the process of microparticulating or dispersing the black colorant, the sulfonated copper phthalocyanine has an effect of improving the microparticulation of the black colorant during dispersion and the dispersion stability after dispersion, because the basic skeleton portion is adsorbed to the pigment surface and the sulfonic acid group increases the affinity with the organic solvent or pigment dispersant.
[0025] The copper phthalocyanine in the sulfonated copper phthalocyanine is not particularly limited as long as it has a structure having a copper phthalocyanine skeleton. For example, the copper phthalocyanine skeleton may have a known substituent such as an alkyl group or a halogen atom. From the viewpoint of ease of introduction of a sulfonic acid group, however, a structure having no substituent is preferable.
[0026] The sulfonated copper phthalocyanine preferably has 0.5 to 3 sulfonic acid groups in the molecule. In this way, by having 0.5 to 3 sulfonic acid groups in the molecule, it is possible to obtain a composition for a black matrix that can provide a coating film with excellent surface resistance. The sulfonated copper phthalocyanine more preferably has 0.5 to 1.5 sulfonic acid groups in the molecule, and further preferably has 0.7 to 1.5 sulfonic acid groups. The number of sulfonic acid groups in the molecule can be calculated based on the ratio of sulfur atoms to copper atoms obtained by elemental analysis.
[0027] As the sulfonated copper phthalocyanine, commercially available products may be used, for example, Solsperse 12000 (both manufactured by Lubrizol Nippon Co., Ltd.) and desodium VALIFAST BLUE 1605.
[0028] The content of the sulfonated copper phthalocyanine is preferably from 0.1 to 20 parts by mass, and more preferably from 1 to 15 parts by mass, relative to 100 parts by mass of the black colorant.
[0029] (Epoxy compounds) The pigment dispersion composition for a black matrix of the present invention contains an epoxy compound. It is presumed that the inclusion of the above-mentioned epoxy compound allows the polyfunctional epoxy resin and the functional groups present on the surface of the carbon black to favorably interact with each other, thereby enabling the formation of a black matrix whose surface resistance value does not decrease even when post-baking is performed at high temperature for a long period of time. However, the present invention should not be construed as being limited to the above mechanism.
[0030] Examples of the epoxy compounds include Epolite 4000, Epolite 3002 (all manufactured by Kyoeisha Chemical Co., Ltd.), Denacol DLC-101, Denacol DLC-202, Denacol EX-141, Denacol EX-142, Denacol EX-145, Denacol EX-146, and Denacol EX-147 (all manufactured by Nagase ChemteX Corporation), GAN, GOT, NC2000-L, NC3000, NC3000-L, NC3000-H, NC3000-FH-75M, NC3100, CER3000-L, XD1000, NC7000L, NC7300L, EPPN-201, EPPN-501H, EPPN-501HY, EPPN502H, and EOC N-1020, EOCN-102S, EOCN-103S, EOCN-104S, CER-1020, RE303S-L, RE310S (all manufactured by Nippon Kayaku Co., Ltd.), jER157S70, jER828, jER1002, jER1032H60, jER1750, jER1007, YX8100-BH30, E1256, E4250, E4275 (all manufactured by Mitsubishi Chemical Corporation), Epicron EXA-9583, Epicron N695, HP4032, HP5000, HP7200L (all manufactured by DIC Corporation), VG3101 (manufactured by Mitsui Chemicals, Inc.), Pototo YH-434L (manufactured by Tohto Kasei Co., Ltd.), VG3101L (manufactured by Air Water Inc.), and the like.
[0031] The epoxy compound is preferably at least one selected from the group consisting of the following formulas (1) to (7). Among the above epoxy compounds, from the viewpoint of forming a black matrix having particularly excellent surface resistance and seal strength, those having a bisphenol skeleton are more preferable, and those having a structure represented by the following formula 2 are even more preferable. [ka]
[0032] The content of the epoxy compound is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, as a mass fraction based on the total solid content of the pigment dispersion composition for black matrix of the present invention. The content of the epoxy resin is preferably 12.0% by mass or less, more preferably 10.0% by mass or less, and even more preferably 9.0% by mass or less, as a mass fraction based on the total solid content of the pigment dispersion composition for black matrix of the present invention.
[0033] (amine compounds with molecular weight of 300 or less) From the viewpoint of forming a black matrix having a high surface resistivity and capable of maintaining the surface resistivity even after post-baking at high temperature for a long period of time, the pigment dispersion composition for black matrix of the present invention further contains an amine compound having a molecular weight of 300 or less, and it is preferred that the amine compound having a molecular weight of 300 or less is an amine compound having a secondary or higher carbon atom within 3 atoms from the nitrogen atom of the amino group and / or an amine compound in which the amino group is connected to one or more aromatic rings via a hydrocarbon group having 3 or less carbon atoms.
[0034] The amine compound having a molecular weight of 300 or less is an amine compound having a secondary or higher carbon atom within 3 atoms from the nitrogen atom of the amino group and / or an amine compound in which the amino group is connected to one or more aromatic rings via a hydrocarbon group having 3 or less carbon atoms. By containing such an amine compound, the electron pair on the nitrogen atom is buried by the bulky substituent, and as a result, the ionicity becomes mild in the neutralization of the amine compound and the copper phthalocyanine sulfonate, so that it is considered that the electrical conduction caused by the ionicity can be suppressed. Also, it is considered that the steric hindrance caused by the bulky substituent suppresses the approach of pigment particles to each other. However, the present invention should not be construed as being limited to the above mechanism.
[0035] The amine compound having a secondary or higher carbon atom within 3 atoms from the nitrogen atom of the amino group is preferably an amine compound having a secondary or higher carbon atom within 3 atoms from the nitrogen atoms of all amino groups present in the amine compound, and specific examples thereof include 1,1,3,3-tetramethylbutylamine, diisopropylamine, triisopropylamine, diisobutylamine, triisobutylamine, diisopentylamine, triisopentylamine, tris(2-ethylhexyl)amine, etc. In addition, "within 3 atoms from the nitrogen atom of the amino group" means that the atom adjacent to the nitrogen atom of the amino group is counted as 1, the atom adjacent to the atom adjacent to the nitrogen atom is counted as 2, and the atom adjacent to the atom adjacent to the atom adjacent to the nitrogen atom is counted as 3.
[0036] Examples of the amine compound in which the amino group is connected to one or more aromatic rings via a hydrocarbon group having 3 or less carbon atoms include 3-phenylpropylamine, 2-phenylpropylamine, 1-phenylpropylamine, 2-phenylethylamine, 1-phenylethylamine, phenylmethylamine, and triphenylmethylamine.
[0037] From the viewpoint of suitably improving the surface resistivity, the amine compound having a molecular weight of 300 or less is preferably at least one selected from 3-phenylpropylamine, 1,1,3,3-tetramethylbutylamine, and triisobutylamine.
[0038] The amount of the amine compound having a molecular weight of 300 or less is preferably 5 to 100 parts by mass, and more preferably 20 to 60 parts by mass, per 100 parts by mass of the sulfonated copper phthalocyanine.
[0039] (Organic solvent) The pigment dispersion composition for a black matrix of the present invention preferably contains an organic solvent. As the organic solvent, organic solvents that have been conventionally used in the field of liquid crystal black matrix resists can be suitably used.
[0040] Specifically, the organic solvent is a solvent that is soluble in water under normal pressure (1.013×10 2 The organic solvents include ester-based organic solvents, ether-based organic solvents, ether ester-based organic solvents, ketone-based organic solvents, aromatic hydrocarbon-based organic solvents, and nitrogen-containing organic solvents, each of which has a boiling point of 100 to 250°C at 250 kPa. If a large amount of an organic solvent having a boiling point exceeding 250°C is contained, when a coating film formed by applying the resist composition for a black matrix obtained from the pigment dispersion composition for a black matrix of the present invention is prebaked, the organic solvent may not evaporate sufficiently and remain in the dried coating film, which may result in a decrease in heat resistance of the dried coating film. Furthermore, if the composition contains a large amount of the organic solvent having a boiling point of less than 100° C., it may become difficult to apply the composition uniformly without unevenness, and a coating film having excellent surface smoothness may not be obtained.
[0041] Specific examples of the organic solvent include ether-based organic solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monobutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, and diethylene glycol methyl ethyl ether; ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene ... Examples of the organic solvents include ether ester organic solvents such as ethylene glycol monoethyl ether acetate; ketone organic solvents such as methyl isobutyl ketone, cyclohexanone, 2-heptanone, and δ-butyrolactone; ester organic solvents such as methyl 2-hydroxypropionate, ethyl 2-hydroxypropionate, ethyl 2-hydroxy-2-methylpropionate, 3-methyl-3-methoxybutylpropionate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, methyl 3-ethoxypropionate, ethyl 3-ethoxypropionate, ethyl ethoxyacetate, ethyl hydroxyacetate, and n-amyl formate; alcohol solvents such as methanol, ethanol, isopropyl alcohol, and butanol; and nitrogen-containing organic solvents such as N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide. These can be used alone or in combination of two or more.
[0042] Among the above organic solvents, in terms of solubility, dispersibility, coatability, and the like, diethylene glycol dimethyl ether, diethylene glycol methyl ethyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, cyclohexanone, 2-heptanone, ethyl 2-hydroxypropionate, 3-methyl-3-methoxybutylpropionate, ethyl 3-methoxypropionate, methyl 3-ethoxypropionate, n-amyl formate, and the like are preferred, with propylene glycol monomethyl ether and propylene glycol monomethyl ether acetate being more preferred.
[0043] (Pigment dispersant) The pigment dispersion composition for a black matrix of the present invention preferably contains a pigment dispersant. The pigment dispersant is a basic group-containing pigment dispersant, and examples of the pigment dispersant that can be used include anionic surfactants, basic group-containing polyester-based pigment dispersants, basic group-containing acrylic-based pigment dispersants, basic group-containing urethane-based pigment dispersants, basic group-containing carbodiimide-based pigment dispersants, and acidic group-containing polymeric pigment dispersants. These basic group-containing pigment dispersants may be used alone or in combination of two or more kinds. Among them, basic group-containing polymeric pigment dispersants are preferred because they provide good pigment dispersibility.
[0044] Specific examples of the basic group-containing polymeric pigment dispersant include: (1) A reaction product of an amino group and / or an imino group of a polyamine compound (e.g., a poly(lower alkylene amine) such as polyallylamine, polyvinylamine, or polyethylene polyimine) with at least one member selected from the group consisting of polyesters, polyamides, and polyesteramides having a free carboxyl group (JP 2001-59906 A), (2) Reaction products of low molecular weight amino compounds such as poly(lower) alkyleneimines and methyliminobispropylamine with polyesters having free carboxyl groups (JP-A-54-37082, JP-A-01-311177), (3) A reaction product obtained by sequentially reacting an isocyanate group of a polyisocyanate compound with an alcohol such as methoxypolyethylene glycol, a polyester having one hydroxyl group such as caprolactone polyester, a compound having two or three isocyanate group-reactive functional groups, and an aliphatic or heterocyclic hydrocarbon compound having an isocyanate group-reactive functional group and a tertiary amino group (JP Patent Publication No. 02-612); (4) A compound obtained by reacting a polymer of an acrylate having an alcoholic hydroxyl group with a polyisocyanate compound and a hydrocarbon compound having an amino group. (5) A reaction product obtained by adding a polyether chain to a low molecular weight amino compound. (6) A reaction product obtained by reacting a compound having an isocyanate group with a compound having an amino group (JP-A-04-210220), (7) A reaction product obtained by reacting a polyepoxy compound with a linear polymer having a free carboxyl group and an organic amine compound having one secondary amino group (JP-A-09-87537). (8) Reaction products of polycarbonate compounds having a functional group capable of reacting with an amino group at one end with polyamine compounds (JP Patent Publication (Kokai) No. 09-194585), (9) Copolymers of at least one selected from methacrylic acid esters or acrylic acid esters, such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, stearyl methacrylate, benzyl methacrylate, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, stearyl acrylate, and benzyl acrylate, at least one basic group-containing polymerizable monomer, such as acrylamide, methacrylamide, N-methylolamide, vinylimidazole, vinylpyridine, and a monomer having an amino group and a polycaprolactone skeleton, and at least one styrene, styrene derivative, and other polymerizable monomer (JP Patent Publication (Kokai) No. 01-164429), (10) Basic group-containing carbodiimide pigment dispersants (International Publication WO04 / 000950), (11) Block copolymers consisting of a block having a basic group such as a tertiary amino group or a quaternary ammonium salt group and a block having no functional group (see the description in JP-A-2005-55814), (12) A pigment dispersant obtained by subjecting a polyallylamine to a Michael addition reaction with a polycarbonate compound (JP-A-09-194585), (13) Carbodiimide-based compounds having at least one polybutadiene chain and at least one basic nitrogen-containing group (JP 2006-257243 A), (14) Carbodiimide-based compounds having at least one side chain having an amide group and at least one basic nitrogen-containing group in the molecule (JP 2006-176657 A), (15) Polyurethane-based compounds having structural units having ethylene oxide chains and propylene oxide chains and having amino groups quaternized with a quaternizing agent (JP 2009-175613 A), (16) A compound obtained by reacting an isocyanate group of an isocyanate compound having an isocyanurate ring in the molecule with an active hydrogen group of a compound having an active hydrogen group in the molecule and having a carbazole ring and / or an azobenzene skeleton, wherein the number of carbazole rings and azobenzene skeletons in the molecule of the compound is 15 to 85% of the total number of isocyanate groups derived from the isocyanate compound having an isocyanurate ring and urethane bonds and urea bonds generated by the reaction of the isocyanate groups with the active hydrogen groups (Patent Application No. 2009-220836); (17) Examples include graft copolymers in which polyether or polyester side chains are introduced into acrylate polymers having amino groups.
[0045] Among the basic group-containing polymeric pigment dispersants, basic group-containing urethane-based polymeric pigment dispersants, basic group-containing polyester-based polymeric pigment dispersants, and basic group-containing acrylic-based polymeric pigment dispersants are more preferred, and amino group-containing urethane-based polymeric pigment dispersants, amino group-containing polyester-based polymeric pigment dispersants, and amino group-containing acrylic-based polymeric pigment dispersants are even more preferred.Among the basic group-containing polymeric pigment dispersants, basic group (amino group)-containing polymeric pigment dispersants having at least one chain selected from the group consisting of polyester chains, polyether chains, and polycarbonate chains are particularly preferred.
[0046] The content of the pigment dispersant is preferably 1 to 200 parts by mass, and more preferably 5 to 100 parts by mass, relative to 100 parts by mass of the black colorant.
[0047] (binder resin) The pigment dispersion composition for a black matrix of the present invention preferably contains a binder resin.
[0048] The binder resin may be a thermosetting resin, a thermoplastic resin, a photopolymerizable compound, an alkali-soluble resin, etc. These may be used alone or in combination of two or more kinds.
[0049] Examples of the thermosetting resins and thermoplastic resins include butyral resins, styrene-maleic acid copolymers, chlorinated polyethylene, chlorinated polypropylene, polyvinyl chloride, vinyl chloride-vinyl acetate copolymers, polyvinyl acetate, polyurethane resins, phenolic resins, polyester resins, acrylic resins, alkyd resins, styrene resins, polyamide resins, rubber resins, cyclized rubbers, epoxy resins, celluloses, polybutadiene, polyimide resins, benzoguanamine resins, melamine resins, and urea resins.
[0050] Examples of the photopolymerizable compound include a monomer having one or more photopolymerizable unsaturated bonds in the molecule, and an oligomer having a photopolymerizable unsaturated bond.
[0051] Examples of the monomer having one photopolymerizable unsaturated bond in the molecule include alkyl methacrylates or acrylates such as methyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, methyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate; aralkyl methacrylates or acrylates such as benzyl methacrylate and benzyl acrylate; alkoxyalkyl methacrylates or acrylates such as butoxyethyl methacrylate and butoxyethyl acrylate; and amino groups such as N,N-dimethylaminoethyl methacrylate and N,N-dimethylaminoethyl acrylate. Examples of usable compounds include alkyl methacrylates or acrylates, methacrylic acid esters or acrylic acid esters of polyalkylene glycol monoalkyl ethers such as diethylene glycol monoethyl ether, triethylene glycol monobutyl ether, and dipropylene glycol monomethyl ether, methacrylic acid esters or acrylic acid esters of polyalkylene glycol monoaryl ethers such as hexaethylene glycol monophenyl ether, isobornyl methacrylate or acrylate, glycerol methacrylate or acrylate, and 2-hydroxyethyl methacrylate or acrylate.
[0052] Examples of the monomer having two or more photopolymerizable unsaturated bonds in the molecule include bisphenol A dimethacrylate, 1,4-butanediol dimethacrylate, 1,3-butylene glycol dimethacrylate, diethylene glycol dimethacrylate, glycerol dimethacrylate, neopentyl glycol dimethacrylate, polyethylene glycol dimethacrylate, polypropylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, dipentaerythritol tetramethacrylate, dipentaerythritol hexamethacrylate, dipentaerythritol pentamethacrylate, and the like. Methacrylate, epoxy methacrylate, bisphenol A diacrylate, 1,4-butanediol diacrylate, 1,3-butylene glycol diacrylate, diethylene glycol diacrylate, glycerol diacrylate, neopentyl glycol diacrylate, polyethylene glycol diacrylate, polypropylene glycol diacrylate, tetraethylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol tetraacrylate, dipentaerythritol hexaacrylate, dipentaerythritol pentaacrylate, epoxy acrylate, and the like can be used.
[0053] As the oligomer having a photopolymerizable unsaturated bond, one obtained by appropriately polymerizing the above-mentioned monomers can be used. The binder resins may be used alone or in combination of two or more kinds.
[0054] From the viewpoints of heat resistance and developability, the binder resin is preferably an epoxy acrylate resin.
[0055] The alkali-soluble resin will be described later.
[0056] The content of the binder resin is preferably 3 to 50% by mass, expressed as a mass fraction relative to the total solid content of the pigment dispersion composition for black matrix of the present invention.
[0057] (Method of manufacturing pigment dispersion composition for black matrix) The pigment dispersion composition for black matrix of the present invention can be produced by adding the above-mentioned various components, mixing and kneading the components. The method for the above-mentioned kneading is not particularly limited, and the kneading may be performed by a known method using, for example, a bead mill, a ready mill, an ultrasonic homogenizer, a high-pressure homogenizer, a paint shaker, a ball mill, a roll mill, a sand mill, a sand grinder, a Dyno Mill, a Dispermat, an SC Mill, a Nanomizer, or the like.
[0058] <Resist composition for black matrix> The present invention also relates to a resist composition for a black matrix obtained from the pigment dispersion composition for a black matrix of the present invention.
[0059] (Pigment dispersion composition for black matrix) The resist composition for a black matrix of the present invention contains the above-mentioned pigment dispersion composition for a black matrix of the present invention. The content of the pigment dispersion composition for black matrix is preferably 30 to 80 mass %, and more preferably 40 to 75 mass %, based on the total mass of the resist composition for black matrix of the present invention.
[0060] (Photopolymerization initiator) The black matrix resist composition of the present invention preferably contains a photopolymerization initiator. The photopolymerization initiator is not particularly limited as long as it can generate radicals or cations by irradiation with active energy rays such as ultraviolet rays or electron beams. Examples of the photopolymerization initiator include 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime)ethanone, benzophenone, N,N'-tetraethyl-4,4'-diaminobenzophenone, 4-methoxy-4'-dimethylaminobenzophenone, 2,2-diethoxyacetophenone, benzoin, benzoin methyl ether, benzoin isobutyl ether, benzyl dimethyl ketal, α-hydroxyisopropyl ether, benzoin methyl ... Examples of photopolymerization initiators include benzophenone-based, thioxanthone-based, anthraquinone-based, and triazine-based photopolymerization initiators such as isobutylphenone, thioxanthone, 2-chlorothioxanthone, 1-hydroxycyclohexyl phenyl ketone, t-butylanthraquinone, 1-chloroanthraquinone, 2,3-dichloroanthraquinone, 3-chloro-2-methylanthraquinone, 2-ethylanthraquinone, 1,4-naphthoquinone, 1,2-benzoanthraquinone, 1,4-dimethylanthraquinone, 2-phenylanthraquinone, and 2-methyl-1[4-(methylthio)phenyl]-2-morpholinopropan-1-one. The above photopolymerization initiators may be used alone or in combination of two or more kinds.
[0061] The content of the photopolymerization initiator is preferably 1 to 20% by mass, expressed as a mass fraction relative to the total solid content of the black matrix resist composition of the present invention.
[0062] (Photopolymerizable compound) The resist composition for a black matrix of the present invention preferably contains a photopolymerizable compound. As the photopolymerizable compound, any of those described in the above-mentioned pigment dispersion composition for black matrix can be appropriately selected and used.
[0063] The content of the photopolymerizable compound is preferably 0.1 to 50 mass % as a mass fraction relative to the total solid content of the black matrix resist composition of the present invention.
[0064] (alkali soluble resin) The black matrix resist composition of the present invention preferably contains an alkali-soluble resin. The alkali-soluble resin preferably acts as a binder for the black colorant and is soluble in a developer, particularly an alkali developer, used in the development process when producing a black matrix.
[0065] The alkali-soluble resin may be a block copolymer. By using a block copolymer, the pigment dispersibility is improved compared to other copolymers, and solubility in PGMEA or an alkaline developer can be imparted. Among these block copolymers, a block copolymer having a block composed of an ethylenically unsaturated monomer having one or more carboxyl groups and a block composed of another copolymerizable ethylenically unsaturated monomer is preferred.
[0066] The block copolymer is not particularly limited, and can be one that has been used in the past.Specific examples of the block copolymer include copolymers of an ethylenically unsaturated monomer having a carboxyl group, such as acrylic acid or methacrylic acid, and at least one ethylenically unsaturated monomer selected from the group of monomers and oligomers such as styrene, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, allyl acrylate, allyl methacrylate, benzyl acrylate, benzyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, glycerol monoacrylate, glycerol methacrylate, N-phenylmaleimide, polystyrene macromonomer, polymethyl methacrylate macromonomer, and carboepoxy diacrylate that can be copolymerized with the ethylenically unsaturated monomer having a carboxyl group, and oligomers. However, it is preferable not to use N-vinylpyrrolidone or monomers containing sulfur element. As the block copolymer, a block resin synthesized by living radical polymerization or anionic polymerization can be used. A portion of the block portions of the block copolymer may be composed of a random copolymer.
[0067] As the alkali-soluble resin, an alkali-soluble cardo resin can also be used. Examples of the alkali-soluble cardo resin include epoxy (meth)acrylate acid adducts having a fluorene skeleton, which are addition products of fluorene epoxy (meth)acrylic acid derivatives and dicarboxylic acid anhydrides and / or tetracarboxylic acid dianhydrides. The alkali-soluble resin may also have a photopolymerizable functional group.
[0068] The acid value of the alkali-soluble resin is preferably from 5 to 300 mgKOH / g, more preferably from 5 to 250 mgKOH / g, further preferably from 10 to 200 mgKOH / g, and particularly preferably from 60 to 150 mgKOH / g, from the viewpoint of development characteristics. In this specification, the acid value is a theoretical acid value, which is a value calculated arithmetically based on the amount of ethylenically unsaturated monomer having a carboxyl group and its content.
[0069] The weight average molecular weight of the alkali-soluble resin is preferably from 1,000 to 100,000, more preferably from 3,000 to 50,000, and even more preferably from 5,000 to 30,000, from the viewpoints of development characteristics and solubility in organic solvents. In the present invention, the weight average molecular weight is a polystyrene-equivalent weight average molecular weight obtained based on GPC. In this specification, the weight average molecular weight is measured using a Water2690 (manufactured by Waters Corporation) as an apparatus and a PLgel 5 μm MIXED-D (manufactured by Agilent Technologies Corporation) as a column.
[0070] The content of the alkali-soluble resin is preferably from 1 to 200 parts by mass, and more preferably from 10 to 150 parts by mass, relative to 100 parts by mass of the black colorant. In this case, if the content of the alkali-soluble resin is less than 1 part by mass, the development characteristics may deteriorate, whereas if the content of the alkali-soluble resin exceeds 200 parts by mass, the concentration of the black colorant decreases relatively, making it difficult to achieve the desired color density as a thin film.
[0071] The alkali-soluble resin preferably does not contain any primary, secondary, or tertiary amino group, and further preferably does not contain any quaternary ammonium group, and more preferably does not contain any basic group. Incidentally, an alkali-soluble resin having a structure other than that of a block copolymer may be blended within a range that does not impair the effects of the present invention.
[0072] (Organic solvent) As the organic solvent, any of the organic solvents described above in relation to the pigment dispersion composition for black matrix can be appropriately selected and used.
[0073] The content of the organic solvent is preferably from 1 to 40 mass %, and more preferably from 5 to 35 mass %, based on the total mass of the black matrix resist composition of the present invention.
[0074] (Other additives) In the black matrix resist composition of the present invention, various additives such as a thermal polymerization inhibitor, an ultraviolet absorber, and an antioxidant can be appropriately used as necessary.
[0075] (Breakpoints) In the pigment dispersion resist composition for black matrix of the present invention, the change in break point between immediately after preparation and after storage at 60°C for one week is preferably within ±3 seconds, more preferably within ±2 seconds, even more preferably within ±1.5 seconds, particularly preferably within ±1.0 seconds, and most preferably within ±0.5 seconds. If the above-mentioned breakpoint change is within ±3 seconds, it can be determined that the data has a sufficient property that the breakpoint does not change depending on the storage time. The above-mentioned breakpoint change can be measured by the following method. The pigment dispersion resist composition for black matrix is applied onto a glass substrate (EAGLE XG) by a spin coater to a film thickness of 1 μm, and pre-baked at 100° C. for 2 minutes. Then, using a photomask with line patterns of 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, and 30 μm, a high-pressure mercury lamp was used to expose the film to a UV cumulative light dose of 50 mJ / cm. 2 A resist film including an exposed portion (cured portion) is produced. Then, using a 0.05% aqueous potassium hydroxide solution (developer), the film was exposed at 23°C and 1.0 kgf / cm 2 Under the condition of a shower pressure of 1000 psi, the time breakpoint at which a development pattern begins to appear is measured. Using the above method, the break point (BP1) immediately after preparation and the break point (BP2) after storage at 60°C for one week are measured, and ΔBP (change in break point) can be calculated using the following formula. ΔBP = BP2 - BP1
[0076] (Method of manufacturing a resist composition for black matrix) As a method for producing the resist composition for a black matrix of the present invention, for example, the pigment dispersion composition for a black matrix of the present invention is prepared, and then the remaining materials are added and stirred and mixed using a stirring device or the like. The method for stirring and mixing is not particularly limited, and known methods such as those using an ultrasonic disperser, a high-pressure emulsifier, a bead mill, a three-roll mill, a sand mill, and a kneader can be used. After the stirring and mixing, the mixture may be filtered through a filter. When preparing the resist composition for a black matrix of the present invention, the black colorant, the epoxy resin, the oxazine compound, and the like described in the pigment dispersion composition for a black matrix of the present invention may be added, if necessary.
[0077] <Black matrix> The black matrix of the present invention is formed from the black matrix resist composition of the present invention.
[0078] The method for forming the black matrix of the present invention is not particularly limited, and for example, the black matrix can be formed by applying the black matrix resist composition of the present invention onto a transparent substrate, drying the composition to form a coating film, placing a photomask on the coating film, and performing image exposure through the photomask, development, and, if necessary, photocuring, or the like.
[0079] Methods for applying, drying, exposing and developing the black matrix resist composition of the present invention can be appropriately selected from known methods. As the transparent substrate, a known transparent substrate such as a glass substrate or a plastic substrate can be appropriately selected and used.
[0080] The thickness of the coating film after drying is preferably 0.2 to 10 μm, more preferably 0.5 to 6 μm, and even more preferably 1 to 4 μm. By setting the thickness within the above range, a predetermined pattern can be suitably developed, and a predetermined optical density can be suitably imparted.
[0081] The black matrix of the present invention is applied to a glass substrate (EAGLE XG) using a spin coater to a thickness of 1 μm, prebaked at 100° C. for 2 minutes, and then exposed to a high-pressure mercury lamp (UV integrated light amount 50 mJ / cm 2 ) and then post-baked at 230°C for 3 hours to produce a black resist pattern consisting of only the solid areas. The surface resistance of the black resist pattern was 1.0×10 14 Ω / □ or more is preferable, 3.0×1014 Ω / □ or more is preferable, and 5.0×10 14 Ω / □ or more is more preferable, and 9.0×10 14 Ω / □ or more is particularly preferable, and 1.0×10 15 It is most preferable that it is Ω / □ or more. The surface resistance is 1.0×10 14 If it is Ω / □ or more, short circuits and current leakage can be suitably prevented. The surface resistance value can be measured using a microammeter R8340 (main body) and a shield box R12702A (optional) (both manufactured by Advance Co., Ltd.).
[0082] The black matrix of the present invention is applied to a glass substrate (EAGLE XG) using a spin coater to a thickness of 1 μm, prebaked at 100° C. for 2 minutes, and then exposed to a high-pressure mercury lamp (UV integrated light amount 50 mJ / cm 2 ), and then post-baked at 230°C for 3 hours and then at 250°C for 1 hour. When a black resist pattern consisting of only the solid areas was produced, the surface resistance was 1.0×10 14 Ω / □ or more is preferable, 2.0×10 14 Ω / □ or more is preferable, and 5.0×10 14 Ω / □ or more is more preferable, and 9.0×10 14 Ω / □ or more is particularly preferable, and 1.0×10 15 It is most preferable that it is Ω / □ or more. The surface resistance is 2.0×10 14 If the resistivity is Ω / □ or more, it can be said that the film has an excellent surface resistivity even after post-baking at high temperature for a long period of time.
[0083] Since the pigment dispersion composition for a black matrix, the resist composition for a black matrix, and the black matrix of the present invention have the above-mentioned properties, they can be suitably used as a black matrix for image display devices, touch panels, and the like. EXAMPLES
[0084] The present invention will be specifically described below using examples, but the present invention is not limited to these as long as it does not deviate from the spirit and scope of application. In the examples, "parts" and "%" represent "parts by mass" and "% by mass", respectively, unless otherwise specified.
[0085] The various materials used in the following examples and comparative examples are as follows. <Black colorant> Carbon black (product name "NEROX305", average primary particle size approximately 28 nm, pH approximately 2.8, manufactured by Orion Engineered Carbons) <Pigment dispersant> LPN22102 (block type pigment dispersant with amino group, solid content 40% by mass, manufactured by BYK-Chemie) <Epoxy compounds> VG3101L (an epoxy compound having the structure of the above formula 2, product name "TECHMORE VG3101L", manufactured by Printec Co., Ltd.) <Amine compounds> 3-Phenylpropylamine (Tokyo Chemical Industry Co., Ltd.) 1,1,3,3-Tetramethylbutylamine (Tokyo Chemical Industry Co., Ltd.) Triisobutylamine (Tokyo Chemical Industry Co., Ltd.) <Binder resin> ZCR-1569H (epoxy acrylate resin, solid content 70% by mass, manufactured by Nippon Kayaku Co., Ltd.) <Organic solvent> PM (Propylene glycol monomethyl ether) PGMEA (Propylene glycol monomethyl ether acetate) <Photopolymerization initiator> OXE02 (product name: Irgacure OXE02, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime)ethanone, manufactured by BASF) <Photopolymerizable compound> DPHA (Dipentaerythritol Hexaacrylate) <Alkali-soluble resin> WR-301 (Product name "WR-301", cardo resin, acid value 100mgKOH / g, solid content 45%, manufactured by ADEKA)
[0086] <Preparation of Dispersion Composition> (Dispersion composition 1) Solsperse 12000 (a sulfonated copper phthalocyanine (containing approximately 0.9 sulfonic acid groups per molecule), manufactured by Lubrizol Nippon Co., Ltd.) and 3-phenylpropylamine were mixed in a mass ratio of 25:8 to obtain a dispersion composition 1. (Dispersion composition 2) Solsperse 12000 (a sulfonated copper phthalocyanine (containing approximately 0.9 sulfonic acid groups per molecule), manufactured by Lubrizol Nippon Co., Ltd.) and 1,1,3,3-tetramethylbutylamine were mixed in a mass ratio of 10:3 to obtain a dispersion composition 2. (Dispersion composition 3) Dispersion composition 3 was obtained by mixing Solsperse 12000 (a sulfonated copper phthalocyanine (containing approximately 0.9 sulfonic acid groups per molecule), manufactured by Lubrizol Japan Co., Ltd.) and triisobutylamine in a mass ratio of 25:11.
[0087] <Dispersion material> Solsperse 12000 (sulfonated copper phthalocyanine (containing approximately 0.9 sulfonic acid groups per molecule), manufactured by Lubrizol Japan) Solsperse 5000 (quaternary ammonium salt of sulfonated copper phthalocyanine (containing approximately 0.9 sulfonic acid groups per molecule), manufactured by Lubrizol Japan) VALIFAST BLUE 1605 (VB1605, sodium neutralized sulfonated copper phthalocyanine, manufactured by Orient Chemical Industries Co., Ltd.)
[0088] <Preparation of Pigment Dispersion Composition for Black Matrix> The materials were mixed to obtain the composition shown in Table 1, and kneaded overnight in a bead mill to prepare a pigment dispersion composition for black matrix.
[0089] [Table 1]
[0090] <Preparation of Black Matrix Resist Composition> Using a high-speed stirrer, the above-mentioned pigment dispersion composition for black matrix and other materials (photopolymerizable compound, alkali-soluble resin, photopolymerization initiator, and organic solvent) were uniformly mixed to the composition shown in Table 2, and then filtered through a filter with a pore size of 3 μm to obtain black matrix resist compositions of the Examples and Comparative Examples.
[0091] <Evaluation test> (Surface resistance value 1) Each of the pigment dispersion resist compositions for black matrix in the Examples and Comparative Examples was applied to a glass substrate (EAGLE XG) using a spin coater to a film thickness of 1 μm, prebaked at 100° C. for 2 minutes, and then exposed to a high-pressure mercury lamp (UV integrated light amount 50 mJ / cm 2 ) and then post-baked at 230° C. for 3 hours to produce a black resist pattern (black matrix) consisting of only solid areas. The surface resistance of each of the prepared black resist patterns was measured using a microammeter R8340 (main unit) and a shield box R12702A (optional unit) (both manufactured by Advance Co., Ltd.). The results are shown in Table 2.
[0092] (Surface resistance value 2) Each of the pigment dispersion resist compositions for black matrix in the Examples and Comparative Examples was applied to a glass substrate (EAGLE XG) using a spin coater to a film thickness of 1 μm, prebaked at 100° C. for 2 minutes, and then exposed to a high-pressure mercury lamp (UV integrated light amount 50 mJ / cm 2 ), and then post-baked at 230° C. for 3 hours and then at 250° C. for 1 hour to produce a black resist pattern (black matrix) consisting only of solid areas. The surface resistance of each of the prepared black resist patterns was measured using a microammeter R8340 (main unit) and a shield box R12702A (optional unit) (both manufactured by Advance Co., Ltd.). The results are shown in Table 2.
[0093] (Breakpoint change) For each of the pigment-dispersed resist compositions for black matrix of the Examples and Comparative Examples, the break point was measured immediately after preparation and after storage at 60° C. for one week by the following method. Each pigment-dispersed resist composition for black matrix was applied onto a glass substrate (EAGLE XG) by a spin coater to a film thickness of 1 μm, and prebaked at 100° C. for 2 minutes. Then, using a photomask with line patterns of 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, and 30 μm, a high-pressure mercury lamp was used to expose the film to a UV cumulative light dose of 50 mJ / cm. 2 A resist film including an exposed portion (cured portion) was produced. Then, using a 0.05% aqueous potassium hydroxide solution (developer), the film was exposed at 23°C and 1.0 kgf / cm 2 The time breakpoint at which a developed pattern began to appear was measured under the condition of a shower pressure of 1000 MPa. The break point immediately after preparation (BP1) and the break point after storage at 60°C for one week (BP2) were used to calculate ΔBP (change in break point) using the following formula. The results are shown in Table 2. ΔBP = BP2 - BP1
[0094] [Table 2]
[0095] In the examples using a pigment dispersion composition for a black matrix containing a black colorant, a sulfonated copper phthalocyanine, and an epoxy compound, it was confirmed that a black matrix whose surface resistance value does not decrease even when post-baked at high temperature for a long period of time can be formed, and a resist composition for a black matrix whose break point does not change depending on storage time can be obtained. It was also confirmed that by satisfying the above condition (B), it is possible to form a black matrix having a high surface resistivity that does not decrease even when post-baked at a high temperature for a long period of time. [Industrial Applicability]
[0096] According to the present invention, it is possible to provide a pigment dispersion composition for a black matrix which can form a black matrix whose surface resistance value does not decrease even when post-baked at high temperature for a long period of time, and which can obtain a resist composition for a black matrix whose break point does not change depending on storage time.
Claims
1. The ink contains a black colorant, a sulfonated copper phthalocyanine, and an epoxy compound, The epoxy compound is at least one selected from the group consisting of the following formulas (1) to (7): Pigment dispersion composition for black matrix. 【Chemistry 1】
2. The pigment dispersion composition for black matrix according to claim 1 , wherein the epoxy compound is represented by the formula (2).
3. 3. The pigment dispersion composition for black matrices according to claim 1, wherein the content of the epoxy compound is 1% by mass or more and 12.0% by mass or less, as a mass fraction with respect to a total solid content of the pigment dispersion composition for black matrices.
4. 4. The pigment dispersion composition for black matrices according to claim 1, further comprising an amine compound having a molecular weight of 300 or less, wherein the amine compound having a molecular weight of 300 or less is an amine compound having a secondary or higher carbon atom within 3 atoms from a nitrogen atom of an amino group and / or an amine compound in which an amino group is connected to one or more aromatic rings via a hydrocarbon group having 3 or less carbon atoms.
5. 5. The pigment dispersion composition for black matrix according to claim 4, wherein the amine compound having a molecular weight of 300 or less is at least one selected from the group consisting of 3-phenylpropylamine, 1,1,3,3-tetramethylbutylamine, and triisobutylamine.
6. 6. The pigment dispersion composition for black matrix according to claim 1, wherein the sulfonated copper phthalocyanine has 0.5 to 3 sulfonic acid groups in the molecule.
7. 7. The pigment dispersion composition for black matrix according to claim 6, wherein the sulfonated copper phthalocyanine has 0.5 to 1.5 sulfonic acid groups in the molecule.
8. 8. The pigment dispersion composition for a black matrix according to claim 1, wherein the black colorant contains carbon black.
9. 9. The pigment dispersion composition for a black matrix according to claim 8, wherein the carbon black is an acidic carbon black.
10. A resist composition for a black matrix obtained from the pigment dispersion composition for a black matrix according to any one of claims 1 to 9.
11. A black matrix formed from the resist composition for a black matrix according to claim 10.
Citation Information
Patent Citations
Active energy ray-curable resin composition, colored spacer for display element and black matrix
JP2014126663A
Black matrix composition and method of manufacturing black matrix using the same
JP2018028630A
Photosensitive resin composition and method for manufacturing substrate with resin film
JP2019070720A
Curable resin composition and electronic part device
JP2020045380A
Pigment dispersion composition for black matrix, and pigment dispersion resist composition for black matrix containing the same
JP2021038289A